“The paper cups Nile”: microplastics and other hazardous substances leached from paper cups: paper cups aquatic environmental bane in the River Nile, Egypt - Eid, Zainab; Mahmoud, Usama M.; Sayed, Alaa El-Din (Frontiers in Environmental Science, 2025)
Recent studies suggest that paper cups may also contribute to environmental pollution, particularly through the release of microplastics (MPs). The Nile River, one of the world’s most vital water sources, faces alarming contamination levels, raising concerns about its ecological health. This study investigated whether paper cups release MPs, ions, and heavy metals into water and assessed the potential impact of MPs on fish. In order to completely comprehend the nature and scope of the issue, 1 L of water was collected from the Nile River in Assiut, Egypt and the paper cups were ripped into tiny pieces. Paper cups were similarly soaked in similar volumes of distilled and tap water. Four months later, the leachate from each trail (three replicates for each) was analyzed to determine and compare the distribution of specific ions, heavy metals and microplastics. In order to clarify the availability of MPs in freshwater fish, the intestines of two common fish species (Oreochromis niloticus and Bagrus bajad) were collected from the River Nile in Assiut and examined. Polyethylene, polystyrene and polypropylene were the three main forms of microplastics identified in water samples from the Nile. Also, paper cups soaked in tap water leached the same three groups of MPs, but in lower amounts. Some microplastics may take longer to biodegrade in water, as evidenced by the absence of other forms of microplastics like rayon and polyvinyl chloride in any of the water samples under investigation. The present findings also indicate a noteworthy accumulation of MPs in the intestines of O. niloticus and B. bajad. In conclusion, these results indicated release of some ions, heavy metals, and microplastics from paper cups into water and the River Nile water is polluted with paper cups which have a negative effect on aquatic organisms. This study brings us one step closer to investigating and fully understanding the nature and extent of the problem posed by paper cups and their effects on the River Nile and freshwater fish, which will ultimately be reflected in human health risks.